Manipulating the film morphology evolution toward green solvent‐processed perovskite solar cells. Issue 4 (31st December 2021) - Shan, Shiqi; Li, Yaokai; Wu, Haotian; Chen, Tianyi; Niu, Benfang; Zhang, Yingzhu; Wang, Di; Kan, Chenxia; Yu, Xuegong; Zuo, Lijian; Chen, Hongzheng
Abstract: High‐performance perovskite solar cells (PVSCs) with low energy consumption and green processing are highly desired, but constrained by the difficulty in morphology control and the poor understanding on morphology evolution mechanisms. To address this issue, here we studied the effect of antisolvents on the perovskite film formation. We found that both the antisolvents and the perovskite composition affect the perovskite film morphology greatly via influencing the intermediate phase, and different perovskite compositions require different antisolvents to reach the optimal morphology. This provides the opportunity to achieve high‐performance PVSCs with green antisolvent, that is, isopropanol (iPA) by changing the perovskite compositions, and leads to a power conversion efficiency (PCE) of 21.50% for PVSCs based on MA0.6 FA0.4 PbI3 . Further, we fabricated "fully green" PVSCs with all layers prepared by green solvents, and the optimal PCE can reach 19%, which represents the highest among PVSCs with full‐green processing. This work provides insight into the perovskite morphology evolution and paves the way toward "green" processing PVSCs. Abstract : Green antisolvent and full‐green solvents‐processed high‐performance perovskite solar cells with efficiencies of 21.5 and 19.5% have been demonstrated by fine tuning the intermediate phase via antisolvent selection and composition engineering.